2006
DOI: 10.1038/sj.ki.5001914
|View full text |Cite
|
Sign up to set email alerts
|

Use of the embedded peritoneal dialysis catheter: Experience and results from a North American Center

Abstract: Since 2000, the Ottawa Hospital Home Dialysis Program has used a variation on the embedded peritoneal dialysis catheter technique described by Moncrief et al. In this paper, we describe our approach to placement of peritoneal access and report our experience with 304 embedded catheters placed between January 2000 and December 2003. We review the advantages and disadvantages of this technique and describe factors that have been important to the success of our program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 22 publications
(20 reference statements)
0
41
0
Order By: Relevance
“…While surgical insertion of PD catheters remains the most common technique worldwide, problems in some PD centers include a lack of timely access to operating facilities, operating staff, and anesthesia services (21,22), plus additional problems when residents without sufficient experience are assigned to perform the procedure (23). Surgical insertion may also often require hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…While surgical insertion of PD catheters remains the most common technique worldwide, problems in some PD centers include a lack of timely access to operating facilities, operating staff, and anesthesia services (21,22), plus additional problems when residents without sufficient experience are assigned to perform the procedure (23). Surgical insertion may also often require hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…Our center places embedded PD catheters several months before the anticipated need for PD (4). Our previously published results have shown an increase in the rate of mechanical obstruction to catheter flow among those catheters that are left buried for .5 months before use (5).…”
Section: Introductionmentioning
confidence: 99%
“…Our published reports of over 400 buried PD catheters have shown that this technique is associated with low rates of surgical, mechanical, and infectious complications (3). Over the years, we have noted from time to time asymptomatic peritoneal leukocytosis with negative effluent cultures immediately after exteriorization of a buried catheter.…”
mentioning
confidence: 91%
“…At the Ottawa Hospital, when the patient is ready to start PD, the catheter is exteriorized by the home dialysis nephrologist at the bedside through a small incision using local anesthetic and under sterile technique. The transfer set is then attached and the patient begins PD training the same day (3). At the Toronto General, the catheter is usually exteriorized a few days to a week prior to training.…”
Section: Methodsmentioning
confidence: 99%